2019
DOI: 10.33087/jagro.v4i2.85
|View full text |Cite
|
Sign up to set email alerts
|

Pembuatan Rorak pada Perkebunan Kopi Arabica (Coffea arabica ) Untuk Meningkatkan Produktivitas

Abstract: High rainfall and soil tillage without applying soil and water conservation techniques (WCT) have led to higher runoff and erosion and washed away top soil that is rich in nutrients needed by plants. This causes soil fertility to decrease over time. This study aims to examine the differences in growth and productivity of Arabica coffee that  the uses of rorak and without rorak. This research was conducted in the farmer's garden which is incorporated in the Barokah farmer group Sungai Jernih Village Gunung 7 Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The dead-end trench application produced 1047.61 kg.ha -1 per year green beans, while the cultivation in land without deadend trench only produced 683.89 kg.ha -1 per year green beans. This result showed that dead-end trench increased the productivity of arabica coffee plants (Satibi et al, 2019).…”
Section: Introductionmentioning
confidence: 81%
“…The dead-end trench application produced 1047.61 kg.ha -1 per year green beans, while the cultivation in land without deadend trench only produced 683.89 kg.ha -1 per year green beans. This result showed that dead-end trench increased the productivity of arabica coffee plants (Satibi et al, 2019).…”
Section: Introductionmentioning
confidence: 81%
“…This is presumably due to silt pit accommodated runoff during wet season, which made the infiltration period longer. Study by Satibi et al (2019) showed that the soil moisture content in coffee fields Influence of Various Soil and Water Conservation Methods on the Moisture Balance at Coffee Plant Root Zone with silt pit was higher (45.91%) when compared to coffee fields without silt pit (28.23%). The total SM was significantly different between all treatment plots in FP on observations of 19 th (Table 1).…”
Section: Soil Moisture Storagementioning
confidence: 99%
“…Influence of Various Soil and Water Conservation Methods on the Moisture Balance at Coffee Plant Root Zone mm). Study by Satibi et al (2019) showed that the silt pit at coffee plantation could increase the soil moisture content (45.91%) when compared to the coffee plantation without the silt pit (28.23%); thereby increased the land productivity by 7,3 Mg.ha -1 .year -1 on the plots with silt pit; while the productivity land on the plots without silt pit was 4,8 Mg.ha -1 .year -1 . Sari (2017) mentions that biopore can increase the activity of soil organisms, thereby increasing soil porosity and infiltration capacity so that soil moisture storage also increases.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the results which showed that the water content far from the root zone had a higher value than the others. Results of the study of Satibi et al (2019) showed that making a silt pit in the coffee plantation was able to increase soil moisture content by 45.91% when compared to without silt pit by 28.23%.…”
Section: Soil Moisture Contentmentioning
confidence: 99%